Randomized phase 2 study of ACE‐083, a muscle‐promoting agent, in facioscapulohumeral muscular dystrophy. Issue 1 (9th May 2022) - Statland, Jeffrey M.; Campbell, Craig; Desai, Urvi; Karam, Chafic; Díaz‐Manera, Jordi; Guptill, Jeffrey T.; Korngut, Lawrence; Genge, Angela; Tawil, Rabi N.; Elman, Lauren; Joyce, Nanette C.; Wagner, Kathryn R.; et al.
Abstract: Introduction/Aims: Facioscapulohumeral muscular dystrophy (FSHD) is a slowly progressive muscular dystrophy without approved therapies. In this study we evaluated whether locally acting ACE‐083 could safely increase muscle volume and improve functional outcomes in adults with FSHD. Methods: Participants were at least 18 years old and had FSHD1/FSHD2. Part 1 was open label, ascending dose, assessing safety and tolerability (primary objective). Part 2 was randomized, double‐blind for 6 months, evaluating ACE‐083240 mg/muscle vs placebo injected bilaterally every 3 weeks in the biceps brachii (BB) or tibialis anterior (TA) muscles, followed by 6 months of open label. Magnetic resonance imaging measures included total muscle volume (TMV; primary objective), fat fraction (FF), and contractile muscle volume (CMV). Functional measures included 6‐minute walk test, 10‐meter walk/run, and 4‐stair climb (TA group), and performance of upper limb midlevel/elbow score (BB group). Strength, patient‐reported outcomes (PROs), and safety were also evaluated. Results: Parts 1 and 2 enrolled 37 and 58 participants, respectively. Among 55 participants evaluable in Part 2, the least‐squares mean (90% confidence interval, analysis of covariance) treatment difference for TMV was 16.4% (9.8%‐23.0%) in the BB group ( P  < .0001) and 9.5% (3.2%‐15.9%) in the TA group ( P  = .01). CMV increased significantly in the BB and TA groups and FF decreased in the TA group. There were no consistent improvements in functional or PRO measures in either group. The most common adverse events were mild or moderate injection‐site reactions. Discussion: Significant increases in TMV with ACE‐083 vs placebo did not result in consistent functional or PRO improvements with up to 12 months of treatment.